The Influence of Islamic Marketing, Lifestyle, and Price on Pre-Loved Clothing Purchases: Intention as a Mediator - Sitepu, Novi Indriyani; Akustia, Syifa Salsabila (Share: Jurnal Ekonomi dan Keuangan Islam, 2024)
This study investigates the influence of Islamic marketing strategies, lifestyle factors, and pricing on pre-loved clothing purchase decisions, mediated by purchase intention. The study employs Structural Equation Modeling (SEM) to analyze data collected through questionnaires distributed to 120 respondents in Banda Aceh City, following a sample size determined by the Hair formula. The findings reveal that purchase intention directly impacts purchasing decisions. Additionally, Islamic marketing strategies, lifestyle factors, and pricing all exert a direct influence on purchase intention. Interestingly, the study identifies that lifestyle factors do not have a significant direct effect on purchasing decisions. Furthermore, the analysis demonstrates that purchase intention partially mediates the relationship between Islamic marketing strategies, lifestyle factors, price, and pre-loved clothing purchase decisions. These results suggest that Islamic marketing strategies can be a valuable tool for businesses operating in the pre-loved clothing market.==============================================================================================================ABSTRAK – Pengaruh Pemasaran Islami, Gaya Hidup, dan Harga terhadap Pembelian Pakaian Pre-Loved: Minat sebagai Mediator. Penelitian ini bertujuan untuk mengkaji pengaruh strategi pemasaran Islam, gaya hidup, dan harga terhadap keputusan pembelian pakaian pre-loved dengan minat beli sebagai mediator. Data dikumpulkan melalui sebaran kuesioner kepada 120 responden di Kota Banda Aceh, yang ditentukan dengan rumus Hair. Analisis data dilakukan dengan menggunakan Structural Equation Modeling (SEM) dalam software AMOS 22. Hasil penelitian menunjukkan bahwa minat beli secara langsung memengaruhi keputusan pembelian. Strategi pemasaran Islam, gaya hidup, dan harga juga secara langsung memengaruhi minat beli. Selain itu, strategi pemasaran Islam secara langsung memengaruhi keputusan pembelian. Namun, gaya hidup tidak menunjukkan pengaruh positif dan signifikan terhadap keputusan pembelian. Lebih lanjut, minat beli memediasi secara parsial pengaruh strategi pemasaran Islam, gaya hidup, dan harga terhadap keputusan pembelian. Oleh karena itu, bisnis preloved disarankan untuk terus menerapkan strategi pemasaran Islam dalam menjalankan usahanya.